Penerapan Teknik Freewriting Untuk Meningkatkan Kemampuan Menulis Cerita Pendek Siswa - Arini Lubis, Asmiah; Nursyaidah, Nursyaidah; Lubis, Anita Angraini; Adila, Dwi (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2026)
This research was motivated by the low Indonesian language proficiency, particularly in short story writing. This is due to the lack of variety in methods and techniques used by teachers during the learning process, which results in students feeling bored with the techniques used. The problem formulation in this study is whether the application of this freewriting technique can improve the short story writing ability for class V students at SDN 0112 Janjlobi. This study aims to determine whether the application of the freewriting technique will be able to improve the short story writing ability for class V students at SDN 0112 Janjilobi. This research is a Classroom Action Research (PTK) with a focus on planning, action, observation, and reflection at SDN 0112 Janjilobi. The subjects were V students at SDN 0112 Janjilobi. The data collection instruments used were tests and observations. The results of this study indicate that the application of the freewriting technique can improve students' short story writing skills. This is evidenced by the increase in the average value and completeness of student learning outcomes, namely in the pre-cycle stage the average was 45 and completeness was 19% (3 out of 16 students). In cycle I meeting I, the average student score was 48 and completeness was 25% (4 out of 16 students). In cycle I meeting II, the average student score was 67 and completeness was 44% (7 out of 16 students). In cycle II, meeting I, the average student score was 69 and the completion rate was 63% (11 out of 16 students). Meanwhile, in cycle II, meeting II, the average student score was 74 and the completion rate was 75% (12 out of 16 students). It can be concluded that the application of the freewriting technique can improve the short story writing skills for class V students at SDN 0112 Janjilobi. For further research, the researcher hopes that the learning process can be further improved so that learning objectives can be achieved.